Missionary women in the straits settlement: intrusion and integration - Toa, Chunyu (Nanyang Technological University, 2023)
Missionary women in the Straits Settlement were allowed a significantly higher amount of agency as compared to their foreign counterparts. This was in part due to the relative unfamilarity the colonial society had with the local population, and also in part due to the prevailing Western societal changes. These women were instrumental in producing knowledge regarding the local natives for the Western world, fuelling the construction and reinforcement of the Orient. At the same time, these missionary women were able to integrate the local women into the wider global Christian network through their usage of native preacher women.